2020
DOI: 10.5539/gjhs.v12n3p12
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Self-Esteem on the Relationship Between Optimism and Life Satisfaction in Final Year University Students

Abstract: This study examined the moderating effect of self-esteem on the relationship between optimism and life satisfaction in final year university students. A correlational survey design was utilized. Two hundred and twenty-three university final year students of a Nigerian university consisting of 124 males and 99 females aged 24.67±2.56 participated in the study. Data were collected with a structured self-report questionnaire containing satisfaction with life scale (α = .82), Rosenberg self-esteem scale (α = .86),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…In addition, individual focus on the expectation of positive results leads to an increase in the quality of life.The results of the current study revealed a partial mediation of self-esteem in the relationship between optimism and quality of life. This result is similar to the result of the Agberotimi and Oduaran (2020) study. The current result explains that the individual's anticipation of good events improves his selfperception.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, individual focus on the expectation of positive results leads to an increase in the quality of life.The results of the current study revealed a partial mediation of self-esteem in the relationship between optimism and quality of life. This result is similar to the result of the Agberotimi and Oduaran (2020) study. The current result explains that the individual's anticipation of good events improves his selfperception.…”
Section: Discussionsupporting
confidence: 91%